PEMBINAAN KEAGAMAAN PADA PENDERITA GANGGUAN MENTAL DAN PECANDU NARKOBA - Dahliyani, Imma (Institut Agama Islam Negeri (IAIN) Salatiga, 2013)
The study is an effort to know how is the way healing method of mentalÂ nuisance victim and drug addict by religious guidance. This research used descriptive qualitative approach. The data is collected by interview, observation, and documentation which are involved in research object. The finding of field shows significant result of establishment by religiousÂ activity (such as performing prayer together, reciting holy Qurâan and shalawat, dzikrul manakib, istighosah, mujahadah, and pray therapy) that influence the victimâs recovery. Based on the result, the researcher draw a conclusion that religious approach can be an alternative way to solve psychological matter, especially such thing related to mental or drug addict nuisance.